Comparative Genomics of the Conjugation Region of F-like Plasmids: Five Shades of F - Fernandez-Lopez, Raul; de Toro, Maria; Moncalian, Gabriel; Garcillan-Barcia, M. Pilar; de la Cruz, Fernando (Frontiers in Molecular Biosciences, 2016)
The F plasmid is the foremost representative of a large group of conjugative plasmids, prevalent in Escherichia coli, and widely distributed among the Enterobacteriaceae. These plasmids are of clinical relevance, given their frequent association with virulence determinants, colicins, and antibiotic resistance genes. Originally defined by their sensitivity to certain male-specific phages, IncF plasmids share a conserved conjugative system and regulatory circuits. In order to determine whether the genetic architecture and regulation circuits are preserved among these plasmids, we analyzed the natural diversity of F-like plasmids. Using the relaxase as a phylogenetic marker, we identified 256 plasmids belonging to the IncF/ MOBF12group, present as complete DNA sequences in the NCBI database. By comparative genomics, we identified five major groups of F-like plasmids. Each shows a particular operon structure and alternate regulatory systems. Results show that the IncF/MOBF12 conjugation gene cluster conforms a diverse and ancient group, which evolved alternative regulatory schemes in its adaptation to different environments and bacterial hosts.